Short Communication: New record of a primitive brachiopod, Lingula sp. in Lubuk Damar, Indonesia - ANANINGTYAS S. DARMARINI; YUSLI WARDIATNO; TRI PRARTONO; KADARWAN SOEWARDI (Biodiversitas Journal of Biological Diversity, 2017)
Darmarini AS, Wardiatno Y, Prartono T, Soewardi K. 2017. Short Communication: New record of primitive brachiopod, Lingula sp. in mangrove ecosystem of Lubuk Damar, Aceh Tamiang, Indonesia. Biodiversitas 18: 1438-1444.. Darmarini AS, Wardiatno Y, Prartono T, Soewardi K. 2017. Short Communication: New record of primitive brachiopod, Lingula sp. in mangrove ecosystem of Lubuk Damar, Aceh Tamiang, Indonesia. Biodiversitas 18: 1438-1444.. This study reports the occurrence of the primitive brachiopod, Lingula in mangrove ecosystem as a new record in Indonesia. Specimens were collected from the mangrove sediment at a depth of between the sediment surface and 20 cm beneath. . Lingula has a glossy shell and oval-ovate shell shape. The color of shell is brownish or greenish. In posterior a point where pedicle occurs is found. The pedicle is a prolongation of the body like an anchor, with varying length, rough, hard and striped texture. Pedicle has soft transparent layer and the edges are covered by the substrate. The inside body of Lingula, there is a lophophore, which is the characteristic of this species The total length of the brachiopod ranges from 3-122 mm. The texture of habitat consists of 39.67% sand, 50.95% silt, and 11.45% clay.